2017
DOI: 10.1177/0886260517737553
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Predictors of Aggressive Behavior Among Men and Women

Abstract: This study examined the relationships among attitude toward violence, self-esteem, emotion dysregulation, anger, and aggression in community men and women and male inmates. Overall, 166 community men, 197 community women, and 100 male inmates completed a battery of questionnaires containing self-reported measures. Self-esteem and attitude toward violence were significant predictors of aggressive behavior, with emotion dysregulation mediating the relationship between self-esteem and the criterion variable. Ange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…The group of clinical psychologists recorded the lowest rates, both of physical violence and non-physical violence. This may be due, on the one hand, to the fact that they are generally less exposed than the nursing staff and the non-medical staff, because they do not require close physical contact, like the nursing staff [7, 16, 40, 44], or bureaucratic procedures, like the administrative staff, which can provoke users’ impatience and discontent [43]. On the other hand, the psychologist’s work implies the need to establish a good therapeutic alliance as part of the intervention, for which an empathic attitude and unconditional acceptance of the patient are essential, which could explain the low frequency of aggressive behaviors [45].…”
Section: Discussionmentioning
confidence: 99%
“…The group of clinical psychologists recorded the lowest rates, both of physical violence and non-physical violence. This may be due, on the one hand, to the fact that they are generally less exposed than the nursing staff and the non-medical staff, because they do not require close physical contact, like the nursing staff [7, 16, 40, 44], or bureaucratic procedures, like the administrative staff, which can provoke users’ impatience and discontent [43]. On the other hand, the psychologist’s work implies the need to establish a good therapeutic alliance as part of the intervention, for which an empathic attitude and unconditional acceptance of the patient are essential, which could explain the low frequency of aggressive behaviors [45].…”
Section: Discussionmentioning
confidence: 99%
“…The anger dimension was also found to be a predictor of aggressive and violent behavior. A recent meta-analytic review confirmed a robust relationship between anger and violent behavior [19]; other authors have demonstrated the fundamental role played by anger in the risk of violence [59] and, in this direction, a recent review suggested that anger treatments are moderately effective to reduce aggression [37].…”
Section: Hostility Anger and Metacognitionmentioning
confidence: 95%
“…A person's sense of self-worth is mostly derived from their professional and social networks. Self-esteem can also be thought of as a global selfassessment indicator that includes both cognitive assessments of general self-worth and emotional self-experiences that come from these assessments (Stefanile et al, 2021). In line with Lyu et al (2019), Self-esteem is defined as a self-evaluation followed by an emotional reaction to oneself.…”
Section: Introductionmentioning
confidence: 99%